Analys of the Analysis of the Influence of Work Ethic and Work Motivation on Employee Work Productivity of Pt. Bayer Indonesia: Motivation, Work Ethic - Rofi'ah Febriani (International Journal of Educational and Life Sciences, 2024)
Work ethic is something that needs to be considered to increase the productivity of PT. Bayer Indonesia employee performance. In addition to work ethic, good motivation is also needed. The purpose The purpose of this research is to find out how much influence work ethic and motivation have. either separately (partially) or together (simultaneously) against employee performance productivity of PT. Bayer Indonesia. The research variable questionnaire was created based on the dimensions and indicators of the research variables distributed to 92 samples from 1200 employees. From the results of the questionnaire answers, scores will be obtained for each independent variable (Ethos and Motivation) and related variables (Productivity) of employees at PT. Bayer Indonesia. The percentage of the influence of work ethic on employee work productivity at PT. Bayer Indonesia is 75%, while motivation has an effect on work productivity at PT. Bayer Indonesia by 38%. While together the influence of work ethic and work motivation on work productivity at PT. Bayer Indonesia is 95%.